How do you interest the public with ironworking artefacts? - (:unkn) unknown (My University, 2023)
Of course, the invention and, above all, the widespread production and use of iron and iron objects throughout the world, and particularly in Africa, has profoundly changed the daily lives of men and women and their relationship with the environment. But let's face it, palaeometallurgical sites present archaeological remains that are difficult for the public to understand. Made up of heaps of metallurgical waste - slag, tuyères and walls - and ruined furnaces - never complete - they are hardly attractive. So how best to present the scientific research being carried out there and the importance of these discoveries in reconstructing the history of humanity, and of metallurgists in particular?As part of my research projects in the Bassar region of Togo, I wanted to collaborate on the production of three media: a comic book, a documentary film and an animation. The aim of the first and last of these was to put the history of metallurgy and metallurgists in an african iron-working region into words and images. The creation of these media goes well beyond scientific work, since it involves collaboration with non-scientists and has to attract an audience while respecting archaeological discoveries. This comic book and this animation attempt to inform and raise awareness of this part of African history, while trying to avoid falling into the fantasies conveyed about the mysterious world of the African blacksmith.
Keywords: African Research